1993
DOI: 10.1161/01.res.72.4.768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dysfunctional vascular endothelium on myocardial performance in isolated papillary muscles.

Abstract: Vascular endothelium has been shown to modify the contractile characteristics of vascular smooth muscle, and endocardial endothelium has been shown to modify the contractile characteristics of adjacent myocardium. In this study, whether vascular endothelium also modifies the contractile characteristics of adjacent myocardium and whether these effects are additive to those of endocardial endothelium were investigated. Rabbit hearts (n=54) were excised and mounted in a Langendorif preparation. Vascular reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…17 Other investigators have shown that similar dysfunction could be obtained by selectively damaging the endothelial monolayer of the coronary bed. 18 At variance with these earlier reports, in the present study, exposure of hearts to ultrasound alone, even at an MI of 1.6, did not produce any LV contractile dysfunction. This is probably because the energy levels used in the present study were considerably lower than those used in the previous reports.…”
Section: Ultrasound-induced Contractile Dysfunctioncontrasting
confidence: 88%
“…17 Other investigators have shown that similar dysfunction could be obtained by selectively damaging the endothelial monolayer of the coronary bed. 18 At variance with these earlier reports, in the present study, exposure of hearts to ultrasound alone, even at an MI of 1.6, did not produce any LV contractile dysfunction. This is probably because the energy levels used in the present study were considerably lower than those used in the previous reports.…”
Section: Ultrasound-induced Contractile Dysfunctioncontrasting
confidence: 88%
“…In vitro and in vivo studies have shown that cardiac endothelium and its paracrine mediators (NO, PGs, ET-1, and other as yet unidentified agents) alter myocardial contractile performance mainly by influencing the time of onset of relaxation, primarily via changes in cardiac myofilament response to calcium. 3,[17][18][19] Consistently, the presented mechanical analysis revealed marked changes in the onset of A, Change in contractile performance parameters (meanϮSEM) from baseline by the combination of the 3 inhibitors of endothelial factors L-NMMA, BQ-123, and indomethacin in papillary muscles from 3 groups of rabbits (control, LPSϩ12h, and LPSϩ36h). B, Change in tHR (ms) from baseline by inhibition of either NO, ET-1, or PG pathways.…”
Section: Discussionsupporting
confidence: 74%
“…Cardiac endothelial cells (vascular and endocardial) are uniquely poised to act as sensors of systemic stress (by virtue of exposure to circulating factors) as well as sensors and regulators of cardiac stress and function (by virtue of their close proximity to cardiac myocytes). The idea that cardiac endothelial cells play a critical role in autocrine/ paracrine regulation of the heart is supported by the finding that removal of either of these types of endothelial cells has significant detrimental effects on the contractile function of the adjacent cardiac myocytes [35]. Despite these important observations, the mechanisms and mediators of these functions of the endothelial cells are largely undefined.…”
Section: Endothelium As a Regulator Of Cardiac Functionmentioning
confidence: 99%
“…In addition to the obviously critical role of supplying oxygen and nutrients to the myocardium, vascular endothelium plays a critical role in maintaining myofilament integrity and myocyte contractility [35]. The relationship between cardiac growth and capillary density has revealed some fascinating concepts demonstrating a tight interrelationship between myocardial and vascular mass in the normal heart, and dysregulation of this relationship in disease states [38].…”
Section: The Relationship Between Cardiac Endothelium and Myocytes: Cmentioning
confidence: 99%